Respiratory syndromes among pilgrims: assessment of Health status and interventions to alleviate respiratory Symptoms - Deris, Zakuan Zainy (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2009)
Background: Acute respiratory symptoms are the commonest problems faced by pilgrims in Makkah. They could result from overcrowding, physical exhaustion and anxiety. The hot-dry atmospheric air exacerbates the problems. Objectives: The aim of the study was to determine the occurrence of acute respiratory symptoms among Malaysian hall pilgrims Methodology: A cross-sectional study was conducted amongst two thousands Malaysian pilgrims. Survey forms were distributed at Madinatul-hullaj, Jeddah where pilgrims stay on transit before returning to Malaysia. Response to the survey was on voluntary basis. The results were analysed using STAT A version 9.0. The denominator was the number of completed survey forms. Results: 394 pilgrims completed and returned the survey forms; 219 males and 173 were females [2 persons did not state their gender]. Only two (0.5%) pilgrims were younger than 10 years and 51 (13.0%) were above 61 years of age. A large majority received influenza vaccination 278 (72.4%). The common underlying diseases were diabetes 48 (12.2%), asthma 35 (8.9%), prolonged cough 34 (8.6%) and rhinitis 28 (7.1 %). In descending order the occurrence of symptoms and their respective 95% confidence intervals were: cough 91.3% (88.0-93.7), runny nose 79.2% (74.9-82.9), sore throat 57.1% (52.1 -61.9) and fever 59.1% (54.2-63.9). Only 3.6% (2.2-5.9) of pilgrims did not suffer from any of these symptoms. Majority had more than two symptoms and longer than 2 weeks duration. The Malaysian hall pilgrims who had single symptom were 9.3% (6.8-12.6), two symptoms 23.7% (19.7-28.1), three symptoms 25.4% (21.4-30.0), and four symptoms 36.5% (31.9-41.4). Only 1.5% (0. 7-3.3) had had hospitalization due to their illness. Conclusion: Acute respiratory symptoms were remarkably common among Malaysian hall pilgrims. The interventional measures to reduce the" morbidity of respiratory related symptoms should be carried out in future Hall seasons.